KDM6 Demethylases and Their Roles in Human Cancers - Hua, Chunyan; Chen, Jiaqing; Li, Shuting; Zhou, Jianan; Fu, Jiahong; Sun, Weijian; Wang, Wenqian (Frontiers in Oncology, 2021)
Cancer therapy is moving beyond traditional chemotherapy to include epigenetic approaches. KDM6 demethylases are dynamic regulation of gene expression by histone demethylation in response to diverse stimuli, and thus their dysregulation has been observed in various cancers. In this review, we first briefly introduce structural features of KDM6 subfamily, and then discuss the regulation of KDM6, which involves the coordinated control between cellular metabolism (intrinsic regulators) and tumor microenvironment (extrinsic stimuli). We further describe the aberrant functions of KDM6 in human cancers, acting as either a tumor suppressor or an oncoprotein in a context-dependent manner. Finally, we propose potential therapy of KDM6 enzymes based on their structural features, epigenetics, and immunomodulatory mechanisms, providing novel insights for prevention and treatment of cancers.